Antibody upstream sequence diversity and its biological implications revealed by repertoire sequencing. (20th October 2021) - Zhu, Yan; Yang, Xiujia; Ma, Cuiyu; Tang, Haipei; Wang, Qilong; Guan, Junjie; Xie, Wenxi; Chen, Sen; Chen, Yuan; Wang, Minhui; Lan, Chunhong; Sun, Deqiang; et al.
Abstract: The sequence upstream of the antibody variable region (antibody upstream sequence [AUS]) consists of a 5′ untranslated region (5′ UTR) and a preceding leader region. The sequence variations in AUS affect antibody engineering and PCR based antibody quantification and may also be implicated in mRNA transcription and translation. However, the diversity of AUSs remains elusive. Using 5′ rapid amplification of cDNA ends and high-throughput antibody repertoire sequencing technique, we acquired full-length AUSs for human, rhesus macaque, cynomolgus macaque, mouse, and rat. We designed a bioinformatics pipeline and identified 3307 unique AUSs, corresponding to 3026 and 1457 unique sequences for 5′ UTR and leader region, respectively. Comparative analysis indicated that 928 (63.69%) leader sequences are novel relative to those recorded in the international ImMunoGeneTics information system. Evolutionarily, leader sequences are more conserved than 5′ UTR and seem to coevolve with their downstream V genes. Besides, single-nucleotide polymorphisms are position dependent for leader regions and may contribute to the functional reversal of the downstream V genes. Finally, the AUGs in AUSs were found to have little impact on gene expression. Taken together, our findings can facilitate primer design for capturing antibodies efficiently and provide a valuable resource for antibody engineering and molecule-level antibody studies.